Thickness of Leaf Anatomical Tissue Dicot Ornamental Plants at Different Light Intensities (International Journal of Scientific Research and Management (IJSRM), 2023)
Different light intensities affect the leaf anatomy. This study aims to measure the thickness of the anatomical tissue of the leaves of six types of dicot ornamental plants at different light intensities. This study used a quantitative experimental method with a completely randomized factorial design (CRD-Factorial). This design consisted of two factors, namely the main factors were six types of plants, namely Codiaeum variegatum (L.) A. Juss., Bougainvillea glabra Choisy, Tabernaemontana divaricata (L.) R, Br. Ex Roem. & Schult., Syzygium paniculatum Gaertn, Excoecaria cochinchinensis Lour., and Aerva sanguinolenta BI. The second factor is the different light conditions (open and shading) with three replications. Parameters measured were total leaf anatomical tissue thickness, upper and lower epidermis, palisade, and spongy using a modified paraffin method from Johansen. Data were analyzed using the CRD-Factorial ANOVA model followed by the LSD test. Correlation done between palisade, spongy, and lower epidermis thickness with total tissue thickness. The results showed that the leaf anatomy of six types of dicot ornamental plants varied. All plants have one layer of upper and lower epidermis tissue. In Codiaeum variegatum (L.) A. Juss., Syzygium paniculatum Gaertn, and Excoecaria cochinchinensis Lour. has two layers of palisade tissue while the Bougainvillea glabra Choisy, Tabernaemontana divaricata (L.) R,Br. Ex Roem. & Schult. and Aerva sanguinolenta BI has one layer of palisade tissue. Meanwhile, the spongy tissue in all plants has one layer of tissue. The thickness of the leaf tissue decreased in the shading area along with the depletion of the palisade, spongy, and lower epidermis tissue as indicated by a correlation from moderately strong to very strong. Shrinkage of palisade tissue, sponges, and lower epidermis is a plant’s attempt to get optimal light in shading areas. The more lower epidermis srink, the thickness of leaf become thin while the thickness of palisade and sponge varied so the thickness of total leaf from each species also varied.